2013
DOI: 10.1111/1365-2435.12152
|View full text |Cite
|
Sign up to set email alerts
|

Why polar gigantism and Palaeozoic gigantism are not equivalent: effects of oxygen and temperature on the body size of ectotherms

Abstract: Summary 1.Organisms of gigantic proportions inhabited the world at a time of a hyperoxic prehistoric atmosphere (Palaeozoic gigantism). Extant giants are found in cold polar waters, with large quantities of dissolved oxygen (polar gigantism). Oxygen is usually deemed central to explain such gigantism. Examples of one category of gigantism are often cited in support of the other, but novel insights into the bioavailability of oxygen imply that they cannot be taken as equivalent manifestations of the effect of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 73 publications
7
167
0
Order By: Relevance
“…This was a consistent pattern, indicated by the nonsignificant three-way interaction term (F 4,248 ¼ 0.53, p ¼ 0.72) when species identity was included as a covariate. This is empirical support for predictions that b is negatively correlated with temperature [7,10,11]. Increased temperature caused an expected increase in metabolism, but this was asymmetric; metabolism in smaller individuals rose relatively more than in larger individuals, reflected in decreasing slope (b) values (e.g.…”
Section: )supporting
confidence: 74%
“…This was a consistent pattern, indicated by the nonsignificant three-way interaction term (F 4,248 ¼ 0.53, p ¼ 0.72) when species identity was included as a covariate. This is empirical support for predictions that b is negatively correlated with temperature [7,10,11]. Increased temperature caused an expected increase in metabolism, but this was asymmetric; metabolism in smaller individuals rose relatively more than in larger individuals, reflected in decreasing slope (b) values (e.g.…”
Section: )supporting
confidence: 74%
“…According to the viscosity hypothesis [97], small aquatic animals have greater difficulty engaging in respiratory ventilation and thus oxygen uptake in colder, more viscous water than do larger animals. Consequently, as water temperature decreases, and viscosity increases, smaller animals should exhibit a greater depression of metabolic rate than that of larger animals, thus resulting in a negative association between temperature and the metabolic scaling slope.…”
Section: Implications Of Results For Theorymentioning
confidence: 99%
“…Yet, comparisons of aquatic and terrestrial species revealed that aquatic species exhibit either equal (Klok and Harrison 2013) or greater (Forster et al 2012) thermal plasticity of body size. According to Verberk and Atkinson (2013), greater thermal plasticity among aquatic species results from unique physical challenges of respiring in water coupled with a greater supply of oxygen in cold water. Yet, our study included samples from cold, hypoxic waters, an environmental scenario ignored by synthetic analyses at the interspecific level.…”
Section: Resultsmentioning
confidence: 99%